Dexrazoxane Treatments Limits Subclinical Cardiac Dysfunction in Childhood Acute Lymphoblastic Leukemia Survivors Exposed to Doxorubicin Treatments. Issue 2 (8th March 2023) - Lapointe, Marc-Olivier; Caru, Maxime; Curnier, Daniel; Raboisson, Marie-Josée; Andelfinger, Gregor; Krajinovic, Maja; Laverdière, Caroline; Sinnett, Daniel; Périé, Delphine
Abstract : Introduction: Doxorubicin leads to dose dependent cardiotoxicity in childhood acute lymphoblastic leukemia (ALL) survivors. We investigated survivors' heart health using echocardiography and evaluated doxorubicin and dexrazoxane treatments on cardiac function. Methods: A total of 196 childhood ALL survivors were stratified (standard risk [SR], high risk with and without dexrazoxane (HR+DEX and HR). We performed a complete transthoracic echocardiographic assessment with M-mode echocardiography, Doppler, and Tissue Doppler. We used 2-dimensional and 3-dimensional echocardiography to measure the left ventricular ejection fraction, whereas myocardial strain imaging was used to obtain global strain indices. Results: Although most cardiac and arterial dimension parameters were not different between groups, a difference was observed in posterior intima of the right carotid ( P =0.017). Diastolic functions analyses reported that LV shortening fraction and left and right ventricular lateral S' wave amplitudes were lower in HR than in SR and HR+DEX groups ( P =0.028, P =0.048, and P =0.005, respectively). The LV lateral E' in diastolic function was lower in the HR than in SR and HR+DEX groups ( P =0.036). The LV end-systolic wall stress was higher in HR than in SR and HR+DEX groups ( P =0.009). A decrease contractility was observed, while the effect was not group specific. Strain rate was not different between groups, as opposed to tissue Doppler measurements. Conclusions: This study showed that dexrazoxane treatments could limit subclinical cardiac dysfunction in childhood ALL survivors, whereas survivors in HR group who did not receive dexrazoxane had potential subclinical cardiac damage observable in heart failure patients. Echocardiographic screening for survivors must be part of the follow-up routine in cardio-oncology.